2021
DOI: 10.1186/s12959-021-00339-x
|View full text |Cite
|
Sign up to set email alerts
|

Optimal authoritative risk assessment score of Cancer-associated venous thromboembolism for hospitalized medical patients with lung Cancer

Abstract: Background Cancer-associated venous thromboembolism (VTE) is common in patients with primary lung cancer. It has been understudied which authoritative risk assessment score of cancer-associated VTE is optimal for the assessment of VTE development in hospitalized medical patients with lung cancer. Methods Patients with lung cancer who had undergone computed tomography pulmonary angiography (CTPA), compression ultrasonography (CUS) of lower and upper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…The Khorana score, the most canonical risk forecast model advocated by current guidelines, was widely used for VTE in patients with malignant tumors [ 4 , 5 ], with the following items: diagnosed as pulmonary carcinoma, body mass index (BMI) ≥35 kg/m 2 , hemoglobin (HB) <100 g/L, white blood cells (WBC) >11 × 10 9 /L, and platelets ≥350 × 10 9 /L [ 6 ]. However, its clinical prediction accuracy has been contentious, so novel predictive markers specifically for lung cancer patients are required to be explored like never before [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Khorana score, the most canonical risk forecast model advocated by current guidelines, was widely used for VTE in patients with malignant tumors [ 4 , 5 ], with the following items: diagnosed as pulmonary carcinoma, body mass index (BMI) ≥35 kg/m 2 , hemoglobin (HB) <100 g/L, white blood cells (WBC) >11 × 10 9 /L, and platelets ≥350 × 10 9 /L [ 6 ]. However, its clinical prediction accuracy has been contentious, so novel predictive markers specifically for lung cancer patients are required to be explored like never before [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it’s essential to seek simple but effective biomarkers for tumor-associated VTE, as well as to develop screening tools for people with gastrointestinal cancer. 7 …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it's essential to seek simple but effective biomarkers for tumor-associated VTE, as well as to develop screening tools for people with gastrointestinal cancer. 7 Substantial clinical studies have revealed that the first six months after the initial diagnosis was the most dangerous period for thrombosis. 8,9 At this stage, tumor burden and injurious therapies lead to the body's hypercoagulable state and vascular endothelial damage that synergistically promote thrombosis.…”
Section: Introductionmentioning
confidence: 99%
“…Fifth, clinical applicability and predictive accuracy are 2 important factors to consider when evaluating a VTE risk assessment score . The new diagnostic strategy proposed in this study had similar diagnostic efficiency and moderately reduced image testing (10%) compared with conventional management.…”
mentioning
confidence: 76%